UNLOCKING THE TRADITION OF KHITBAH (ENGAGEMENT) IN RURAL ISLAMIC FAMILY - Abdul Halim; Asmad Hanisy (International Conference on Humanity Education and Society (ICHES), 2022)
ABSTRACTBeing a sakinah, mawaddah, warahmah family is the main goal of those who have carried out a marriage. In social life, it is not legal if someone carries out a marriage procession without starting with khitbah or or, in society called a fiance. This is the main door to enter the marriage room even though it is not like that, because actually the fiance is one of the efforts towards the occurrence of marriage, the meaning is, with the fiance, it is a sign that he already has one. Therefore, this study uses qualitative research methods with the type of case study research to be able to directly describe the circumstances, characteristics of the facts (individuals, groups and circumstances) that occur in society, so that an overview of the actual situation can be obtained, related to the dynamics of engagement among rural Muslims. When researcher conducted observations, interviews, regarding engagement, The researcher has found that there were traditions or habits, for example: choosing a mate, looking at origins, seeing the day and date, shaking hands, visiting each other, spending the night, walking together, together in a quiet place (khalwat).Keywords: Dynamics, Engagement, Rural Islamic Family